The role of the humanities in the Bologna idea of a university: learning from the American model? - Eckhardt Larsen, Jesper (Revista Española de Educación Comparada, 2006)
The Humboldtian idea of a university has, for better or for worse, served as a blueprint for the past two centuries of university development in large parts of Europe. It entails the idea of a unity between research and personal cultivation (Bildung) that indeed has its shortcomings. Since the advent of a strong specialization and theorization the humanities have largely abandoned the more educational function, Bildung in its educational and ethical sense.The American liberal arts college- and university tradition on the other hand,particularly at the bachelor level, has traditionally separated the purely educational readings of a humanities ‘canon’ from the more scholarly pursuits of the humanities. Recent debates on the humanities show these differences across the Atlantic. While the highly specialized humanities in Europe have great problems proving their relevance in a modern society and job-market, the humanities in America are mostly discussed in terms of their educational accountability. Could the Bologna process be an occasionfor the European bachelor to be remodelled along the lines of the American liberal arts model? Could the humanities prove their relevance to non specialists in European higher education? La idea humboldtiana de la universidad ha sido, para bien o para mal, una referencia para el desarrollo universitario en una gran parte de Europa durante los dos siglos pasados. Implica un concepto de unión entre investigación y formación (Bildung) que, efectivamente, tiene sus defectos. Desde la llegada de una fuerte especialización y teorización, las Humanidades han abandonado, en su mayor medida, la función educacional, Bildung en su sentido ético. Por otra parte, la tradición universitaria de las Artes Liberales americanas, particularmente a nivel de Licenciatura, ha diferenciado la lectura puramente educacional del «canon», del meramente académico. Debates recientes han mostrado la existencia de esta diferenciación. Mientras que las altamente especializadas Humanidades en Europa tienen grandes dificultades en mostrar su relevancia en la sociedad moderna y el mercado de trabajo, en Norteamérica son consideradas, mayoritariamente, bajo los términos de su responsabilidad educacional. ¿Podría el Proceso de Bolonia ser una ocasión para que las Licenciaturas europeas sean remodeladas siguiendo el modelo americano de las Artes Liberales? ¿Podrían las Humanidades mostrar su relevancia a quienes sean inexpertos en Educación Superior Europea?